Reducing variation in decomposition odour profiling using comprehensive two‐dimensional gas chromatography. Issue 1 (January 2015) - Perrault, Katelynn A.; Stefanuto, Pierre‐Hugues; Stuart, Barbara H.; Rai, Tapan; Focant, Jean‐François; Forbes, Shari L.
<x xml:space="preserve">Abstract</x> (J. Sep. Sci. 2015, 38 (1), 73–80) DOI: 10.1002/jssc.201400935 This cover picture illustrates the main areas in which challenges are met in decomposition odour profiling; these lead to decreased consensus in the volatile organic compound profile produced during the decomposition of human or animal remains. A project design is required that uses appropriate replicates and controls, followed by valid collection and analysis methods of odorous compounds. Comprehensive two‐dimensional gas chromatography (GC × GC) data is useful for this purpose, providingmore accurate analyses than traditional one‐dimensional gas chromatography, yet complicates the data processing steps required. Data processing and statistical analyses of comprehensive two‐dimensional data can be challenging and a data handling approach was developed to enhance confidence in the results. Principles from this approach may be applied with success to other areas of volatile organic compound profiling to permit standardisation of data processing methods. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>